Structural correlates of survival in Progressive Supranuclear Palsy - Street, Duncan (Parkinsonism Relat Disord, 2023)
INTRODUCTION: Many studies of the Richardson’s syndrome phenotype of progressive supranuclear palsy (PSP) have elucidated regions of progressive atrophy and neural correlates of clinical severity. However, the neural correlates of survival and how these differ according to variant phenotypes are poorly understood. We set out to identify structural changes that predict severity and survival from scanning date to death. METHODS: Structural magnetic resonance imaging data from 112 deceased people with clinically defined ‘probable’ or ‘possible’ PSP were analysed. Neuroanatomical regions of interest volumes, thickness and area were correlated with ‘temporal stage’, defined as the ratio of time from symptom onset to death, time from scan to death (‘survival from scan’), and in a subset of patients, clinical severity, adjusting for age and total intracranial volume. Forty-nine participants had post mortem confirmation of the diagnosis. RESULTS: Using T1-weighted magnetic resonance imaging, we confirmed the midbrain, and bilateral cortical structural correlates of contemporary disease severity. Atrophy of the striatum, cerebellum and frontotemporal cortex correlate with temporal stage and survival from scan, even after adjusting for severity. Subcortical structure-survival relationships were stronger in Richardson’s syndrome than variant phenotypes. CONCLUSIONS: Although the duration of PSP varies widely between people, an individual’s progress from disease onset to death (their temporal stage) reflects atrophy in striatal, cerebellar and frontotemporal cortical regions. Our findings suggest magnetic resonance imaging may contribute to prognostication and stratification of patients with heterogenous clinical trajectories and clarify the processes that confer mortality risk in PSP.